CDM 2015 : a practical guide for architects and designers - Bussey, Paul (Riba Publishing, 2015)
This is the designer's essential guide to implementing the new CDM 2015 regulations. It provides both a straightforward overview of the key changes and new duty holders, including the Principal Designer, as well as full colour diagrams and annotated plans which demonstrate how to apply the principles in the real world. As the regulations come into force it aims to reassure those fearing a change in their obligations by outlining easy to use practical tools which will integrate the philosophy of the new regulations - of proportionate response, creative solutions and collaborative working - into day-to-day practice. It's designed as a concise and handy quick reference guide, easy to carry around on site or use at your desk, translating what can be dry and often impenetrable legislation into a set of simple, intuitive, design friendly and safe messages.